PWE-057 Impaired neutrophil phagocytic capacity in patients with advanced cirrhosis is related to the development of ammonia-induced neutrophil swelling. (23rd September 2015) - Taylor, N J; Abeles, R; Hussein, M; Ma, Y; Wendon, J; Shawcross, D L
Abstract : Introduction: Neutrophil phagocytic dysfunction is associated with increased risk of infection and mortality in patients with cirrhosis. Increased bacterial translocation from the gut generates a proinflammatory response in patients with cirrhosis and the resulting cytokine milieu leads to neutrophil priming and conformational changes in binding ligands which alters phagocytic capacity. A recent study has also shown that ammonia exposure induces neutrophil swelling and impairs phagocytosis. (1) This longitudinal study aimed to characterise the relationship between neutrophil function and volume, plasma cytokine profile and ammonia in a cohort of patients with advanced liver cirrhosis undergoing assessment for liver transplantation (LT), and 72 h following LT, compared to healthy controls (HC) (n=8). Methods: Neutrophils were isolated from 26 patients with end-stage cirrhosis at baseline, and 72 h following LT (n=7/26) during the 18-month follow-up period. Phagocytosis was analysed by flow cytometry using FITC-labelled E coli and anti-CD16-PE IgG1 as a neutrophil stain. Neutrophil volume was measured by comparing the forward scatter of 10 000 gated neutrophils in their resting state using flow cytometry. Clinical data, blood biochemistry, arterial ammonia and microbial cultures were collected. Cytokine analysis for TNF-α, IL-1β, IL-6, IL-8, IL-10 and IL-17 were performed using ELISA. Results: Neutrophil phagocytosis was significantly impaired in patients with advanced cirrhosis (p=0.007) and was associated with an 11.2% increase in neutrophil volume. In those who underwent uncomplicated LT, neutrophil volume and phagocytic capacity normalised within 72 h. Phagocytic impairment correlated with increasing plasma concentrations of the proinflammatory cytokines TNF-α (p=0.01), IL-6 (p=0.008) and IL-17 (p=0.03) and the anti-inflammatory cytokine IL-10 (p=0.08) but not with IL-1β or IL-8. Severe phagocytic impairment also predicted those who went on to develop sepsis and multi-organ dysfunction. Elevated arterial ammonia concentrations directly correlated with worsening neutrophil phagocytic dysfunction (r 2 =0.01, p=0.02). Conclusion: These data demonstrate that impaired phagocytic capacity in patients with advanced cirrhosis is related to the development of ammonia-induced neutrophil swelling and is associated with poor outcomes in those who do not undergo LT.